Incidental arrhythmias during atrial fibrillation screening in a hospital-based patient population. (19th May 2022) - Goulouti, E; Lam, A; Nozica, N; Elchinova, E; Spirito, A; Servatius, H; Noti, F; Seiler, J; Baldinger, S; Haeberlin, A; Babken, A; Franzeck, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Screening for atrial fibrillation may reveal other, incidental arrhythmias of relevance. We sought to describe such incidental arrhythmias in the prospective STARFIB cohort study, which screened for silent atrial fibrillation in hospitalized patients aged 65-84 years. Method: Patients included in the STARFIB cohort study had up to three 7-day Holter ECGs, performed in two-month intervals. We analysed all the 7-day Holter ECGs of study participants for the presence of one of the following incidental arrhythmias: 1) sick-sinus-syndrome (SSS), defined as sinus arrest of ≥3 seconds duration; 2) second or higher degree atrioventricular block (AVB); 3) sustained atrial tachycardia of ≥30 seconds duration (AT); and 4) sustained ventricular tachycardia of ≥30 seconds duration (VT). Results: A total of 2'077 Holter ECGs were performed in 794 patients (mean age 74.7 years; 49% females), resulting in a mean cumulative duration of an analyzable ECG signal of 414±136 hours per patient. We found incidental arrhythmias in 94 patients (11.8%). Among these were SSS in 14 patients (1.8%), AVB in 41 (5.2%), AT in 41 (5.2%), and VT in two (0.3%). The median pause duration in SSS was 4 seconds and SSS resulted in pacemaker implantation in one patient with a pause of 9 seconds duration. The most severe type of AVB found per patient was second degree AVB type Wenkebach in 23 patients (2.9%), second degree AVB type Mobitz or 2:1 AV conduction in 10 patients (1.3%) and complete AVB in 8 (1%; maximum pause 18 seconds). AVB led to pacemaker implantation in 9 patients (1.1%). The median duration and heart rate of AT was 2.2 minutes and 144 bpm, respectively. Initiation of betablocker therapy was recommended in 3 patients (0.4%) due to symptomatic AT. The duration and heart rate of VT was 3 minutes at 216 bpm in one patient and 38 seconds at 150 bpm in another. The former patient with VT experienced syncope and an ICD was implanted, whereas in the latter the betablocker dose was increased. One patient died from a non-cardiac cause during a Holter ECG, which showed progressive bradycardia and finally asystole. Conclusion: Incidental arrhythmias were frequently discovered during screening for atrial fibrillation and resulted in device therapy in 1.4% of our cohort patients.